The Effect of Using Duolingo Application Towards Students’ Vocabulary Mastery at the Eighth Grade of SMPN 2 Banjarsari Lebak-Banten - Puput Permatasari; Ade Sudirman; Tatu Munawaroh (Journal of English Language Learning, 2022)
The purpose of this research was to find out the emperical evidence of The Effect of Using Duolingo Application Toward Students’ Vocabulary Mastery at The Eighth Grade of SMPN 2 Banjarsari Lebak-Banten In Acaddemic Year 2021/2022. In this research, the quantitative methode was used and the research design was a quasi-experimental. To conduct the research, 76 students of eighth grade student of SMPN 2 Banjarsari Lebak academic year of 2021/2022 are choosen as the sample in this research. They were VIII A class as the experimental class, and VIII B class as the control class. Each class consisted of 25 students. This number was taken as the sample of this research by using Mr.Excel and SPSS 25. Duolingo application was used as an instrument in the experimental class while the control class uses the Hello English Application. Based on the calculation, the post-test mean scores of the experimental class was 70.12 while that of the control class was 59.36. The researcher got the result from testing with SPSS 25 t-test obtained the t-count =6.301in control class and signification value (p-value)=0.000 < a =0.05, and with t-test obtained the t-count= 6.463 in experimental class and significant value (p-value) =0.000 < a = 0.05 Ha is accepted and Ho is rejected. The result indicated that using Duolingo is effect towards students’ vocabulary mastery and had a moderate effect at the eighth grade of students SMPN 2 Banjarsari Lebak in the acaddemic year of 2021/2022.